A LEARNING MODEL DEVELOPMENT ON THE COURSE OF MULTIMEDIA BASED COMPUTER NETWORKING ON THE INFORMATICS ENGINERING DEPARTMENT OF UHAMKA - Sugema, Sugema (Prosiding Seminar Nasional Berseri, 2017)
This research is aimed at developing an effective learning model for â€œthe multimediaÂ  based computer networkingâ€ and increasing the studentsâ€Ÿ learning achievements The method used in this research is the Research and Development (R & D) with the approach of Instructional Development Model (MPI) developed by Suparman which is much influenced by Dick and Carey Model. The instruments used in this research are questionnaire and interview. The Result of this research shows that a learning model for â€œMultimedia based Computer Networkâ€ has been developed in which it includes learning substances in the form of printed books and multimedia based learning. The final product of the developed model had been through the expert validation process, whose estimation results are 88.94%, 88.69%, and 89.77%. Meanwhile results of individual evaluation, small group evaluation, and field tests show 89.00%, 89.58%, and 88.54%. As the post-test score is higher than pre-test score, it means the learning model of â€œMultimedia based Computer Networkingâ€ is very feasible and effective to use and can increase the studentsâ€Ÿ learning achievements of UHAMKA Informatics Engineering Department.